Differential expression of the receptors for thyroid hormone, thyroid stimulating hormone, vitamin D and retinoic acid and extracellular signal-regulated kinase in uterus of rats under influence of sex-steroids - Sayem, Abu Sadat Md; Giribabu, Nelli; Karim, Kamarulzaman; Si, Lay Khaing; Muniandy, Sekaran; Salleh, Naguib (Elsevier, 2018)
Sex-steroids play important role in modulating uterine functions. We hypothesized that these hormones affect expression of proteins in the uterus related to thyroid hormone action. Therefore, changes in expression levels of receptors for thyroid hormone (TRα-1 and TRβ-1), thyroid stimulating hormone (TSHR), vitamin D (VDR) and retinoid acid (RAR) as well as extracellular signal-regulated kinase (ERK1/2) in uterus were investigated under sex-steroid influence. Methods: Two rat models were used: (i) ovariectomised, sex-steroid replaced and (ii) intact, at different phases of oestrous cycle. A day after completion of sex-steroid treatment or following identification of oestrous cycle phases, rats were sacrificed and expression and distribution of these proteins in uterus were identified by Western blotting and immunohistochemistry, respectively. Results: Expression of TRα-1, TRβ-1, TSHR, VDR, RAR and ERK1/2 in uterus was higher following estradiol (E2) treatment and at estrus phase of oestrous cycle when E2 levels were high. A relatively lower expression was observed following progesterone (P) treatment and at diestrus phases of oestrous cycle when P levels were high. Under E2 influence, TRα, TRβ, TSHR, VDR, RAR and ERK1/2 were distributed in luminal and glandular epithelia while under P influence, TSHR, VDR abn RAR were distributed in the stroma. Conclusions: Differential expression and distribution of TRα-1, TRβ-1, TSHR, VDR, RAR and ERK1/2 in different uterine compartments could explain differential action of thyroid hormone, TSH, vitamin D, and retinoic acid in uterus under different sex-steroid conditions.